Tm:YAG crystal-derived double-clad fibers – A hybrid approach towards high gain and high efficiency Tm lasers - Martin Leich; Robert Müller; Sonja Unger; Anka Schwuchow; Jan Dellith; Adrian Lorenz; Jens Kobelke; Matthias Jäger (Optical Materials: X, 2022)
The hybrid approach of combining a Tm:YAG laser crystal with an amorphous fused silica tube is investigated to evaluate the suitability of the resulting crystal-derived fibers for efficient double-clad fiber lasers. The fabrication process and fiber properties of these Tm fibers are investigated, focusing on the dependence of the active fiber properties on the incorporated Tm3+ concentration. Crystal rods with different doping concentrations (TmxY1-x)3Al5O12 (x = 0.02, 0.05 and 0.08) were used as starting core material for fiber drawing. The investigated fibers are mechanically stable and result in a fairly homogenous and amorphous core glass with optical absorption and emission spectra that are similar to conventional Tm:Al doped silica fibers. Regarding laser properties with 790 nm cladding pumping, we could achieve a maximum slope efficiency of 47% with an output power of 4 W. The fiber laser results are compared to a conventionally fabricated double-clad Tm fiber prepared by Modified Chemical Vapor Deposition and solution doping. To the best of our knowledge, we demonstrate the highest laser output and the highest efficiency obtained from a Tm:YAG crystal-derived fiber.